A Novel Homozygous Mutation of the Acid-Labile Subunit (IGFALS) Gene in a Male Adolescent - Şükran Poyrazoğlu; Vivian Hwa; Firdevs Baş; Andrew Dauber; Ron Rosenfeld; Feyza Darendeliler (Galenos Yayincilik, 2019)
Acid-labile subunit (ALS) forms ternary complexes with insulin like growth factor-1 (IGF-1) and IGF-binding protein-3 (IGFBP-3) and is essential for normal circulating IGF-1 levels. The IGFALS gene encodes the ALS and mutations in IGFALS cause ALS deficiency. We describe a patient with ALS deficiency with a novel homozygous frameshift mutation in IGFALS presenting with short stature and delayed puberty but ultimately achieving an adult height (AH) comparable to his target height (TH). A 15.25 year old boy presented with short stature (149.9 cm, -3.04 standard deviation score). The patient had a low circulating IGF-1 concentration, extremely low IGFBP-3 concentration, insulin resistance and osteopenia. The peak growth hormone (GH) response to GH stimulation test was high (31.6 ng/mL). Sequencing of IGFALS revealed a novel, homozygous, frameshift mutation (p.Ser555Thrfs.19). His mother and elder sister were heterozygous carriers. Although he had delayed puberty and short stature at the onset of puberty, he reached his TH and an AH similar to those of his heterozygous mother and sister. The heterozygous carriers had normal or low IGF-1 concentrations and low IGFBP-3 concentrations but not as markedly low as that of the patient. They had normally timed puberty, insulin metabolism and bone mineral density (BMD). The phenotype of ALS deficiency is quite variable. Despite short stature and delayed puberty, patients can achieve normal pubertal growth and AH. ALS deficiency may cause osteopenia and hyperinsulinemia. Heterozygous carriers may have normal prenatal growth, puberty, insulin metabolism and BMD.